Estratégias de controle de corrente e amortecimento ativo para conversores conectados à rede elétrica - Braga Júnior, Adailton (2023)
This work presents contributions in two topics about the control of grid-tied inverters. The first one deals with active damping in inverters with LCL filter by developing a technique called Hybrid Active Damping. This technique uses the capacitor current feedback and the feedforward action of the point of common coupling voltage in the control structure. By using these two terms, it is possible to increase the damping of the resonant poles. Then, two methods for choosing the gains are shown, where one is based on the position of the dominant pole of the system, and the other, using Particle Swarm Optimization. Besides, the region/limits of estability are defined for damping gains. The second subject is the current control using a super-twisting sliding mode (STSM) controller. First, the controller for the inveter with L filter is developed. Later, it is extended to the inveter with LCL filter using multiloop approach. In this, the STSM is to control the internal current of the inverter while its reference is generated by an external loop. Simulation and experimental results are shown. Both methods showed satisfactory results.